Routledge handbook of the contemporary Philippines - Thompson, Mark R. 1960-; Batalla, Eric C. (New York Routledge Taylor & Francis Group, 2018)
"The Philippines is a fascinating example of a 'poor country democracy' where issues of economic development and poverty, political participation and stability as well as ethnicity and migration are crucial. The Routledge Handbook of Contemporary Philippines provides a comprehensive overview of the current political, economic, social and cultural issues of the country. The Handbook is divided into the following four sections concentrating on a different aspect of the Philippines: Domestic politics, Foreign relations, Economics and social policy, Cultures and movements. Chapters discuss the political parties and contested elections, as well as dynasties and local governance in the Politics section, and the Economics section looks at topics such as international political economy, industrial policy and economic nationalism. The section on Philippine society highlights the women's movement and gender issues, and goes on to concentrate on religion, culture and customs. The Philippines is confronted with many foreign challenges, and the final section focuses on the relationship the country has with China, Japan, Europe and the USA. Written by leading experts in the field, the Handbook provides students, scholars and policymakers of Southeast Asia with an interdisciplinary resource on the evolving politics, society and economics of the Philippines"-- Provided by publisher.
Clientelism revisited / Masataka Kimura -- Patrons, bosses, dynasties, and reformers in local politics / John T. Sidel -- Party and party system institutionalization / Allen Hicken -- Combating corruption / Jon S.T. Quah -- The civil service : weaknesses and constructive informal practices / Rupert Hodder -- House of clans : political dynasties in the legislature / Julio C. Teehankee -- Pork transmogrified : the unending story of particularistic spending / Ronald D. Holmes -- Congress : separate but not equal / Diana J. Mendoza and Mark R. Thompson -- The presidency : a relational approach / Mark R. Thompson -- The judiciary under threat / Eric Vincent C. Batalla, Michelle Sta. Romana, and Karen Rodrigo -- Civil-military relations : norming and departures / Rosalie Arcala Hall -- Continuity despite change : foreign relations between the Philippines and the United States / Howard Loewen -- From distant to antagonistic neighbor : 21st century Philippine-China relations / Renato Cruz de Castro -- Towards strategic partnership : Philippines-Japan relations after seventy years / Dennis D. Trinidad -- Diaspora diplomacy / Joaquin Jay Gonzalez III -- Bypassing industrial development : the economy since the lost decade / Eric Vincent C. Batalla -- Capital flight / Edsel L. Beja Jr -- The changing configuration of capitalism / Antoinette R. Raquiza -- Economic nationalism and its legacy / Yusuke Takagi -- Technocracy and class politics in policy-making / Teresa S. Encarnacion Tadem -- The allure of Pantawid Pamilya : the conditional cash transfer program / Ma. Victoria R. Raquiza -- Informality and legality in women's livelihoods in Baguio City / B. Lynne Milgram -- Persistent poverty and elite-dominated policymaking / David G. Timberman -- From pamilya to grasya : microfinance / Asuncion Sebastian -- A syncretic culture / Paul A. Rodell -- Gender, nation and Filipino Catholicism past and present / Coeli Barry -- Between rights protection and development aggression : indigenous peoples / Oona Paredes -- The resilience of the peasantry / Eduardo C. Tadem -- The middle class in society and politics / Temario C. Rivera -- Non-governmental organizations (NGOs) in the post-Marcos era / Gerard Clarke -- Crossovers double-crossed : NGOs, semi-clientelism, and political reform / Ben Reid -- The left : struggling to make a comeback / Nathan Quimpo -- Trade unions : free but weak / Carmel Veloso Abao -- The women's movement : policy issues, influence and constraints / Diana Mendoza -- Bangsamoro secessionism / Rizal G. Buendia -- Moro insurgency and third party mediation / Bruce E. Barnes -- The problem with the national(ist) method / Patricio N. Abinales.
Includes bibliographical references and index.
Keywords: Philippines -- Politics and government -- 21st century; Philippines -- Social conditions -- 21st century; Philippines -- Economic conditions -- 21st century; Philippines -- Foreign relations